Segmenting tourists by expenditure patterns: An instrument for enhancing tourism economic benefits on a Portuguese World Heritage site - Serra, Jaime (2018)
The study aims to identify the homogenous groups of visitors that prevail in a WHS destination based on expenditure patterns and furthermore at contributing to the development of marketing strategies to enhance the economic development of this cultural destination.